Pengaruh VCO terhadap Kualitas Plastik Biodegradable Berbasis Selulosa Bakteri Sorbitol dari Air Kelapa - Anjaly, Azzahra Nurfadillah; Putra, Ananda (Mahesa Research Center, 2024)
Plastic is a material that is widely used by society today, causing environmental problems, so a solution is needed so that it does not harm the environment, namely biodegradable plastic. This plastic is an environmentally friendly type of plastic because it is easily degraded by microorganisms. This research was carried out in-situ using FTIR and in this research, various VCO volumes of 2 ml, 4 ml, 6 ml and 8 ml were used with the addition of 30% sorbitol as a plasticizer. Based on the test results, it shows an elongation value of 15.08%, an elasticity value of 1264.41 Mpa, and a tensile strength value of 133.98 Mpa with variations in the addition of 8 mL of VCO. This tensile strength value meets the SNI standard for synthetic plastics, namely in the range of 24.7-302 Mpa. The addition of more and more VCO had an effect on the biodegradation test, where on day 15 the plastic had completely decomposed. In the FTIR functional group analysis, no new functional groups were formed, and in the analysis using XRD when adding VCO, the percentage of plastic crystals was greater, namely 98.02%, compared to bacterial cellulose, which was only 97.01%, and bacterial cellulose-sorbitol, which was 95.79%.